Image storage and retrieval using color quantization method - Mandal, Koushik Kanti; Islam, Md. Rafiqul; Md. Sap, Mohd. Noor; Khatun, Fahmida; Reza, Md. Parvez (Penerbit UTM Press, 2005)
Color is the most dominant and distinguishing visual feature for image. We propose a compact color descriptor here, which is based on the observation that a small number of colors are sufficient to characterize the color information in an image region. The image is segmented by our proposed segmentation algorithm, which uses the compact color descriptor .The result of the experiment shows that the developed segmentation algorithm produces better performances as compared with the existing segmentation algorithm. After segmentation the color features are extracted from the segmented image. Finally the color features are stored in the database using a special type of indexing method for storing and retrieval of image features.